2008
DOI: 10.1021/jp8009113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to FePt Assemblage and Synthesis

Abstract: FePt nanoparticles have been assembled on the surface of MCM-41 silicates. The incorporation resulted in highly dispersed particles. Under thermal treatment for 1 h at temperatures up to 560 °C, no signs of agglomeration occurred. The silicates have also been used as a template to assist in the solution synthesis of FePt particles. The resultant particles were distributed over the surface and possibly inside the silcate pores with a range of sizes (3−10 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…2 (d) and (e)), we can see that particles are found across the surface of the material, however they tend to occur as clusters rather than being fully distributed as in the Fe-MCM system and the previously studied FePt MCM-41 material. 5,7 The clusters of nanoparticles are not large aggregates, rather individual particles that are packed closely together in a region of space, retaining their size. Further analysis of the Fe-puralox material found both areas of well distributed particles across the alumina surface (graphical abstract) and revealed some individual particles distributed across the surface next to a larger cluster (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 (d) and (e)), we can see that particles are found across the surface of the material, however they tend to occur as clusters rather than being fully distributed as in the Fe-MCM system and the previously studied FePt MCM-41 material. 5,7 The clusters of nanoparticles are not large aggregates, rather individual particles that are packed closely together in a region of space, retaining their size. Further analysis of the Fe-puralox material found both areas of well distributed particles across the alumina surface (graphical abstract) and revealed some individual particles distributed across the surface next to a larger cluster (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5,7 Reactions were deemed complete when the hexane became colorless. For the iron oxide materials, the solution was still highly coloured after six hours of stirring only becoming clear after being left overnight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Fuller and his coworkers firstly reported the crystalline structures of PBA in 1930s. [12][13][14][15] Minke and Blackwell have revealed the single crystalline morphology of PBA and found that the polymorphic phenomenon of PBA, that is, PBA can crystallize into the a-form, b-form, and a mixture of both two crystals under different conditions. 16,17 The lattice parameters of two types of crystalline unit cells of PBA have been identified.…”
Section: Introductionmentioning
confidence: 99%